Comparison of Oxytocin Massage and Banana Flower Consumption in Increasing Breast Milk Volume - Hastuti, Novianti Tri; Intan, Dara; Andarini, Sri; Indrawan, I Wayan Agung (Indonesian Journal of Human Nutrition, 2024)
Insufficient breast milk production often occurs during the first week postpartum due to psychological stress, inadequate stimulation of prolactin and oxytocin hormones, and nutritional aspects of the mother’s diet. Efforts to improve and increase breast milk production include providing back massage to induce a relaxing sensation and fulfilling the needs for a balanced nutritious diet, which can effectively stimulate the release of prolactin and oxytocin hormones. This research aims to compare the effectiveness of oxytocin massage and banana flower consumption in increasing breast milk volume. This study used true experimental with a pre-post test design (excluding a control group) and involved 32 postpartum mothers with low-stress levels and low to medium socioeconomic status. Breast milk volume was evaluated by breast pumping for 30 minutes and measuring the output with a measuring cup. Data were analyzed using an independent t-test. There was a 6.375 cc increase in breast milk volume in the banana flower consumption group compared to the oxytocin massage group. However, statistically, both treatments had similar effects, as there were no significant differences between the groups (p = 0.519). Therefore, both oxytocin massage and banana flower consumption can be considered effective alternatives for increasing breast milk volume.